Teoria części czasowych – tezy i argumentacje - Grygianiec, Mariusz (Filozofia Nauki, 2009)
In the paper the most popular arguments in favour of the doctrine of temporal parts are presented and analysed. The author discusses the following arguments: (i) from analogy; (ii) from ontological parsimony; (iii) from intrinsic change; (iv) from mereological change; (v) against presentism; (vi) from time travel; (vii) from vagueness; (viii) from coincidence. The main aim of the paper is to show - in the light of examined arguments - that the 3D-ism/4D-ism equivalence thesis might be treated as a well-founded conjecture.